2016
DOI: 10.18203/2320-6012.ijrms20161746
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of soil transmitted helminths from rural field practice area of a tertiary care center from northern India

Abstract: Background: Soil-transmitted helminths (STH) are a major public health problem in our country, affecting the physical growth and cognitive development. STH infections are considered a leading cause of sickness, absenteeism and disability adjusted life years lost. Aim of the study was to assess the prevalence and risk factors of soil transmitted helminths (STH) in Farrukhabad district, India. Methods: A total of 1203 study subjects from 602 eligible households fulfilling the eligibilty criteria. Thus equal numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Practicing open defecation was also a risk factor of increased STH infection in our study. This result is in accordance with researches reported from India [ 42 ], Indonesia [ 21 ], Vietnam [ 43 ], Nigeria [ 44 ], and Kenya [ 41 ]. The ova of STH are present in contaminated human feces.…”
Section: Discussionsupporting
confidence: 92%
“…Practicing open defecation was also a risk factor of increased STH infection in our study. This result is in accordance with researches reported from India [ 42 ], Indonesia [ 21 ], Vietnam [ 43 ], Nigeria [ 44 ], and Kenya [ 41 ]. The ova of STH are present in contaminated human feces.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that children with untrimmed nger nails were more likely to be infected (p = 0.001) than those with trimmed nger nails. Our nding agree with previous studies (6,40,41). Increased risk of infection for children with untrimmed nger nails is because long nails can hide contamined soil obtained by child during play.…”
Section: Discussionsupporting
confidence: 93%
“…The STHs infection is most prevalent among young children and women of reproductive age in the rural region of Nepal 16 – 18 as a long standing health burden of the country 19 . In this light, a systemic review from Nepal found the pooled prevalence of 1.53% for hookworm, 4.23% for roundworm, and 2.89% for whip worm after 2004 20 .…”
Section: Introductionmentioning
confidence: 99%